2012
DOI: 10.1007/s10509-012-1310-4
|View full text |Cite
|
Sign up to set email alerts
|

On the depolarization asymmetry seen in giant radio lobes

Abstract: The depolarization asymmetry seen in double-lobed radio sources, referred to as the Laing-Garrington (L-G) effect where more rapid depolarization is seen in the lobe with no visible jet as the wavelength increases, can be explained either by internal differences between the two lobes, or by an external Faraday screen that lies in front of only the depolarized lobe. If the jet one-sidedness is due to relativistic beaming the depolarization asymmetry must be due to an intervening Faraday screen. If it is intrins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In fact, a recent study by Bell & Comeau (2012) found, for sources exhibiting the Laing-Garrington effect, that the jet brightness asymmetry on kiloparsec scales cannot be explained by beaming and therefore must be intrinsic (in cases where the estimated kiloparsec-scale outflow speeds are close to 0.1c). They conclude that a Laing-Garrington effect due to intrinsic differences in the Faraday rotating material within radio galaxy lobes cannot be discounted.…”
Section: External Depolarization Modelmentioning
confidence: 99%
“…In fact, a recent study by Bell & Comeau (2012) found, for sources exhibiting the Laing-Garrington effect, that the jet brightness asymmetry on kiloparsec scales cannot be explained by beaming and therefore must be intrinsic (in cases where the estimated kiloparsec-scale outflow speeds are close to 0.1c). They conclude that a Laing-Garrington effect due to intrinsic differences in the Faraday rotating material within radio galaxy lobes cannot be discounted.…”
Section: External Depolarization Modelmentioning
confidence: 99%
“…Recent observations of Centaurus A by O'Sullivan et al (2013) provide evidence of depolarisation across radio lobes from the presence of a significant amount of thermal gas within the lobes. Bell & Comeau (2013) examine a sample of radio sources exhibiting the Laing-Garrington effect and show that the depolarisation cannot be explained by beaming. Farnes et al (2014) compared total intensity spectral indices with polarised spectral indices to show that there are two populations of polarised radio sources: core-and jetdominated sources.…”
Section: Environments Of Polarised Radio Sourcesmentioning
confidence: 99%